Application of stretching techniques in physical rehabilitation of football players with traumas of upper and lower limbs - Doroshenko, E.Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study and experimentally test effectiveness of application of stretching as auxiliary not specific component of complex rehabilitation of football players with traumas of limbs. Material: experiment covered 186 sportsmen of 14-17 years old age. Quantitative indicators of limbs’ traumas and damages were registered in competition and training processes during yearly macro-cycle by results of processing of official competitions’ records and by medical records of football players. Results: application of stretching techniques in training process and in football players’ physical rehabilitation permitted to reduce quantitative indicators of traumas of upper and lower limbs from 18 (season 2012-2013) to 7 cases (season 2013-2014). Indicators of football players trauma’s relapses reduced by 7.93 %. In structure of upper and lower limbs’ traumas of younger age groups indicators of lower limbs’ traumas prevail. In older age groups traumas of upper limbs prevail. Conclusions: application of stretching techniques in football players’ training process permitted to certain extent to optimize indicators of lower limbs’ traumas.